Dissimilatory reduction of sulfate, nitrate and nitrite ions by bacteria Desulfovibrio sp. under the influence of potassium dichromate - O. M. Moroz; S. O. Hnatush; G. V. Yavorska; G. I. Zvir (Regulatory Mechanisms in Biosystems, 2022)
In the process of anaerobic respiration, sulfate reducing bacteria, besides sulfates, can use other electron acceptors: nitrates, nitrites, oxidized forms of heavy metals, in particular, hexavalent chromium, which are harmful for organisms. Selection of pollutant-resistant stains of this kind of bacteria isolated from technogenically altered ecotopes, capable of reductive transformation of various nature pollutants, is an especially relevant task for the creation of new effective remediation biotechnologies. The purpose of this work was to investigate the regularities of usage of sulfate, nitrate or nitrite ions by bacteria of the Desulfovibrio genus, isolated from Yavorivske Lake, at conditions of simultaneous presence in the medium of another electron acceptor – Cr(VI), to establish a succession of electron acceptors’ reduction by investigated sulfidogenic bacteria and to evaluate the efficiency of their possible application in technologies of complex purification of the environment from metal, sulfur and nitrogen compounds. Bacteria were grown under anaerobic conditions for 10 days in Kravtsov-Sorokin medium without Mohr’s salt. To study the efficiency of sulfate, nitrate, or nitrite ions’ reduction at simultaneous presence in the medium of Cr(VI), bacteria were sown in media with Na2SO4×10H2O, NaNO3, NaNO2 or K2Cr2O7 to final SO42–, NO3–, NO2– or Cr(VI) concentration in the medium of 3.47 (concentration of SO42– in medium of standard composition) or 1.74, 3.47, 5.21, 6.94, 10.41 mM. Biomass was determined turbidimetrically, and the concentrations of sulfate, nitrate, nitrite, ammonium ions, hydrogen sulfide, Cr(VI), Cr(ІІІ) in cultural liquid were determined by spectrophotometric method. It has been established that Cr(VI) inhibits the biomass accumulation, sulfate ions’ reduction and hydrogen sulfide production by Desulfovibrio sp. after simultaneous introduction into the medium of 3.47 mM SO42– and 1.74–10.41 mM Cr(VI). In the medium with the same initial content (3.47 mM) of SO42– and Cr(VI), bacteria reduced 2.1–2.3 times more Cr(VI) than sulfate ions with Cr(III) production at concentrations up to 2.2 times higher than hydrogen sulfide. It has been shown that K2Cr2O7 inhibits the biomass accumulation, the nitrate ions reduction and the ammonium ions production by bacteria after simultaneous addition into the medium of 3.47 mM NO3– and 1.74–10.41 mM Cr(VI) or 1.74–10.41 mM NO3– and 3.47 mM Cr(VI). In the medium with the same initial content (3.47 mM) of NO3– and Cr(VI) bacteria reduced 1.1–1.3 times more nitrate ions than Cr(VI) with the production of ammonium ions at concentrations up to 1.3 times higher than that of Cr(III). It has been established that K2Cr2O7 inhibits the biomass accumulation, the nitrite ions’ reduction and the ammonium ions’ production by bacteria after simultaneous addition into the medium of 3.47 mM NO2– and 1.74–10.41 mM Cr(VI) or 1.74–10.41 mM NO2– and 3.47 mM Cr(VI). In the medium with the same initial content (3.47 mM) NO2– and Cr(VI) the reduction of Cr(VI) by bacteria practically did not differ from the reduction of nitrite ions (was only slightly lower – up to 1.1 times), almost the same concentrations of trivalent chromium and ammonium ions in the cultural liquid were detected. The processes of nitrate and nitride reduction, carried out by bacteria of Desulfovibrio genus, were revealed to be less sensitive to the negative influence of sodium dichromate, as compared with the process of sulfate ions’ reduction, which in the medium with 3.47 mM SO42– and 1.74–10.41 mM Cr(VІ) decreased by 3.2–4.6 times as compared with this process in the medium with only Na2SO4×10H2O. The investigated strains of bacteria are adapted to high concentrations of toxic pollutants (up to 10.41 mM) and therefore are promising for application in technologies of complex environment purification from hexavalent chromium, sulfur and nitrogen compounds.